Improving the Dispersity of Nano-silica from Rice Hull Ash in Organic Solvents by a New g-Methacryloxypropyltrimethoxy Silane Solution - Li, Yulin (Asian Journal of Chemistry, 2012)
Improving the dispersity of nano-silica from rice hull ash in organic solvents by different g-methacryloxypropyltrimethoxy silane solutions was investigated. The possible principle of the solvent polarity influencing the dispersity of nano-silica in organic solvents was proposed. The optimum solution was g-methacryloxypropyltrimethoxy silane water solution (0.4 mol/L). The transparency of the optimum modified nano-silica powder anhydrous alcohol solution (0.1 wt. %) was 91.4 %. The dispersity of nano-silica in anhydrous alcohol, CH2Cl2, CCl4, cyclohexane and liquid paraffin increased from 0, 0, 0, 0 and 0.1 to 11.2, 11.3, 11.4, 11.4 and 11.6 g/100 mL after surface modification.